A deletion in nephronophthisis 4 (NPHP4) is associated with recessive cone-rod dystrophy in standard wire-haired dachshund - Wiik, Anne Caroline; Wade, Claire; Biagi, Tara; Ropstad, Ernst-Otto; Bjerkås, Ellen; Lindblad-Toh, Kerstin; Lingaas, Frode (Genome Research, 2008)
Cone-rod dystrophy is a retinal degenerative disorder occurring naturally in man and dog. Here we identify a novel gene for early-onset cone-rod dystrophy in the wire-haired dachshund. For the first time, we use genome-wide association-based Sibling Transmission Disequilibrium Test (sibTDT) analysis of only 13 discordant sib-pairs to identify a single significantly associated 6.5-Mb region (PrawTDT = 4.8 × 10−5, PgenomeTDT = 6 × 10−4) on canine chromosome 5, containing more than 70 genes. Segregation studies using microsatellites in the candidate region including additional meiosis supported the sibTDT analysis but could not further reduce the area. Candidate gene resequencing identified a 180-bp deletion in exon/intron 5 of NPHP4 (nephronophthisis 4, also known as nephroretinin). RT-PCR analysis of NPHP4 in cases and controls showed exon skipping of exon 5, resulting in a truncated protein that retains the binding domain interacting with nephronophthisis 1 (also known as nephrocystin-1) in the kidney but lacks the domain interacting with RPGRIP1 in retina. We suggest that this deletion in the canine NPHP4 gene is the cause of cone-rod dystrophy in the standard wire-haired dachshund. In humans, mutations in NPHP4 have been associated with simultaneous eye and kidney disease. Here we describe the first naturally occurring mutation in NPHP4 without additional kidney disease. Further studies will permit elucidation of the complex molecular mechanism of this retinopathy and the development of potential therapies.